2020
DOI: 10.29333/ejmste/8941
|View full text |Cite
|
Sign up to set email alerts
|

Locating Personal Pedagogical Content Knowledge of Science Teachers within Stories of Teaching Force and Motion

Abstract: A narrative inquiry approach was adapted to study teacher's experiences of planning and teaching force and motion topics. Oral narrative data were collected through interview conversations between the researcher and the teachers about their experiences of planning and teaching force and motion concepts. Narrative analysis technique suggested by Polkinghorne, was employed to develop stories of teaching force and motion-that acceded access to their pPCK. and comprised of small entities of knowledge-pedagogical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Such presentation of science in critical documents, it is believed, creates an impression amongst science teachers to the extent that other equally important aspects about the goals and purpose of science teaching seem subsumed into this. As argued by Azam (2020) and Friedrichsen and Dana (2005), contexts such as curriculum materials, school ethos, etc., play a significant role in shaping the beliefs of the teachers which they articulate or manifest during teaching. Similarly, Suh and Park (2017) indicate that the policies and socio-political priorities that teachers are exposed to tend to influence what teachers conform to in terms of beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such presentation of science in critical documents, it is believed, creates an impression amongst science teachers to the extent that other equally important aspects about the goals and purpose of science teaching seem subsumed into this. As argued by Azam (2020) and Friedrichsen and Dana (2005), contexts such as curriculum materials, school ethos, etc., play a significant role in shaping the beliefs of the teachers which they articulate or manifest during teaching. Similarly, Suh and Park (2017) indicate that the policies and socio-political priorities that teachers are exposed to tend to influence what teachers conform to in terms of beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…While this might be taken as a misalignment of goals of science, the general view is that this observation suggests that goals of science are topic-specific. Azam (2020) noted that teachers' approach to teaching science must necessarily be different due to the demands of the nature of the concepts inherent in each topic as shaped by the curriculum and context. What this means is that for specific topics, a researcher would be able to observe specific goals being manifested during teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Within the landscape of teachers' knowledge base, Shulman (1987) pointed to PCK as the most prominent component of teacher knowledge that is essential for teaching. PCK refers to teachers' knowledge and skills as it relates to representing particular scientific concepts, by using powerful representations and illustrations so that it becomes easy for students to understand (Azam, 2020;Fischer et al, 2012;Morrison & Luttenegger, 2015). Azam (2020) referred to this conception as topic-specific pedagogical construction (TSPC).…”
Section: Research Focusmentioning
confidence: 99%
“…PCK refers to teachers' knowledge and skills as it relates to representing particular scientific concepts, by using powerful representations and illustrations so that it becomes easy for students to understand (Azam, 2020;Fischer et al, 2012;Morrison & Luttenegger, 2015). Azam (2020) referred to this conception as topic-specific pedagogical construction (TSPC). Therefore, PCK is a collection of TSPCs that a teacher develops during teaching of a particular topic, such as force concepts, over a long time.…”
Section: Research Focusmentioning
confidence: 99%
“…This study and many other studies have demonstrated that pedagogical content knowledge is very particular to each teacher, concepts being taught and is much more than merely subject matter knowledge and that it grows through time due to teaching experience. During the teaching process, each tutor's PCK is unique in that it demands tutors to transform their subject content knowledge for teaching purposes (Azam, 2020;Shulman, 1986).…”
Section: What Pck Was Exhibited By Science Tutors Of the Colleges Of ...mentioning
confidence: 99%